A Novel Subthreshold Voltage Reference Featuring 17ppm per °C TC within -40°C to 125°C and 75dB PSRR - Jiang, Jize (2016)
Subthreshold voltage references are increasingly prevalent in power-critical applications due to their low-voltage and ultra-low-power attributes. However, the effective temperature range of state-of-the-art subthreshold voltage references remains undesirably narrow for low temperature coefficient (TC) operation and/or their PSRR is low - thereby severely limiting their range of applications. In this paper, we present a novel subthreshold voltage reference embodying a novel paralleled `2-Transistor' structure and a novel auxiliary amplifier. The former serves to facilitate low TC within a wide temperature range, and the latter for high PSRR and low line-sensitivity. The proposed design achieves low TC of 17ppm/°C within a wide effective temperature range of -40°C to 125°C, and high PSRR of 75dB and low line-sensitivity of 0.3%/V with minimum 0.5V supply voltage and 32nW power consumption. Both the TC and PSRR parameters are, at this juncture, the best performance compared to reported subthreshold voltage references, but with a slight power penalty.